Total thyroidectomy vs radical thyroidectomy with functional lymphadenectomy in thyroid cancer: Evaluation of recurrence 3 years after the surgical procedure (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
This study is based on evaluating the effectiveness of these procedures, total thyroidectomy vs radical thyroidectomy with functional lymphadenectomy in thyroid cancer, their relationship with the recurrence of patients after three years of performing them.Retrospective study of patients admitted to the National Oncology Institute Dr. Juan Tanca Marengo (SOLCA Hospital in the city of Guayaquil) from January 2006 to December 2008 with a diagnosis of thyroid cancer, who have completed follow-up at 6.12 ,24 or 36 months. It is vital for scientific research to compare two treatments, in this case surgical procedures to draw relevant conclusions to improve patient management and avoid the number of complications.Patient data were collected from the clinical history, including age, sex, ultrasound report, pathological diagnosis (follicular, papillary, undifferentiated, medullary carcinoma), laboratory data (thyroid hormones, thyroglobulin), stage according to TNM classification, surgical procedure used (total or radical thyroidectomy with functional lymphadenectomy), use of radioactive iodine, postoperative complications (recurrent laryngeal nerve injury, hypoparathyroidism), follow-up (months) and presence or absence of recurrence in each of these. After collecting the patients, after selection by inclusion and exclusion criteria, they were separated into two groups for analysis: Group A underwent total thyroidectomy, and Group B underwent radical thyroidectomy with functional lymphadenectomy.
Keywords: total thyroidectomy; radical thyroidectomy